The perfect and imperfect clocks approach to performance analysis of basic timestamp ordering in distributed databases - Christos Bouras; Paul Spirakis (ICCI'93, Sudbury, Ontario, Canada, 1993)
Locking and timestamping are two popular approaches to concurrency control in databases systems. Although more than a dozen analytic performance studies of locking techniques have recently appeared in the literature, analytic performance study of timestamp–based concurrency algorithms largely remains an unexplored area. This work presents a model of a distributed database system which provides the framework to study the performance of timestamp ordering concurrency control. We exhibit an analytical solution, which has been tested with extensive simulation. The accuracy seems to be very high. We assume perfect and also imperfect clocks for synchronization and quantify the way in which local clock inaccuracies affect the phenomenon of transaction conflicts. In particular, we derive a lot of interesting performance measures such as probability of abort, throughput and others.